2003
DOI: 10.3346/jkms.2003.18.2.204
|View full text |Cite
|
Sign up to set email alerts
|

Activated Mast Cells Infiltrate in Close Proximity to Enteric Nerves in Diarrhea-predominant Irritable Bowel Syndrome

Abstract: Mast cells (MC) may be one factor influencing the response of visceral afferent nerves to mechanical and chemical stimuli. The aim of this study was to evaluate the degree of infiltration and activity of colonic MC in irritable bowel syndrome (IBS). Biopsy specimens were obtained from the cecum and rectum of 14 diarrhea predominant IBS and 14 normal controls. Electron microscopy was used to determine the number of intact and degranulated colonic MC and to quantify these separately according to the distance bet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
71
0
10

Year Published

2005
2005
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(84 citation statements)
references
References 33 publications
3
71
0
10
Order By: Relevance
“…and rectum. 48,64,68,[78][79][80] These results are particularly robust for the caecum (100% of studies, 6/6) and the colon (80% of studies, 8/10), where mast cell densities can be anywhere from 50% to more than 100% higher than in healthy control patients. When available, individual data from caecum and colon samples indicate that the proportion of abnormal values (values that would be considered as outliers in healthy control datasets) in IBS patients is high, which suggests that overlap with normal tissue is limited.…”
Section: Key Pointsmentioning
confidence: 60%
See 1 more Smart Citation
“…and rectum. 48,64,68,[78][79][80] These results are particularly robust for the caecum (100% of studies, 6/6) and the colon (80% of studies, 8/10), where mast cell densities can be anywhere from 50% to more than 100% higher than in healthy control patients. When available, individual data from caecum and colon samples indicate that the proportion of abnormal values (values that would be considered as outliers in healthy control datasets) in IBS patients is high, which suggests that overlap with normal tissue is limited.…”
Section: Key Pointsmentioning
confidence: 60%
“…Two studies have reported a correlation between mast cell density and increased intestinal permeability in IBS patients. 39,71 Finally, several studies have correlated mast cell number with the severity of abdominal pain symptoms, 64,68,73,116 especially when mast cells were found close to enteric nerves. 68,73 Further investigation is required to determine the activation state of mast cells (e.g.…”
Section: Immune Activation In Ibs Patientsmentioning
confidence: 99%
“…These findings, associated with increased mast cell degranulation, increased spontaneous release of MC tryptase and histamine 1 and increased proximity of MC to enteric nerves in IBS, suggest a role for MC in the disturbed, sensorimotor function characteristic of this condition (3,16,26,39,40,41,58) . The proximity of MC to enteric nerves suggests that MC mediators have increased potential to activate enteric neurons (39) .…”
Section: Discussionmentioning
confidence: 98%
“…In patients with irritable bowel syndrome (IBS) the number of mucosal mast cells (MMC) in terminal ileum and caecum is increased [51,52]. The degranulation rate of MMC in close proximity to nerves was reported to be significantly higher than degranulation of MMC distant from nerve fibers in the colorectal specimens of diarrhea predominant IBS patients [53]. Moreover, a positive correlation was found between the severity of abdominal pain and the proximity of MMC and nerve fibers in IBS patients [35].…”
Section: Endogenous Proteases and Pain Related To Protease-activated mentioning
confidence: 92%